Safeguarding of Goods During Railway Shipping - V. Lomotko, D; O. Kovalov, A; V. Kovalova, O; V. Shuldiner, J (International Journal of Engineering and Technology, 2018)
The definition of estimation criterion of rolling stock availability for certain freight loading is given in this work. The level of commercial availability of cars is proposed as a criterion. The graphic display of the availability level of cars for loading depending on the service life of a car and with account for corresponding repair works and maintenance is represented. The dependence of the type of goods or the group of goods on the level of commercial car availability required for safeguarding during transportation of goods, for safety of operation and continuity of the rolling stock is introduced to provide the corresponding level of commercial rolling stock availability for the freight owner. The variant of the requirement formation for provision of cars using the category of commercial availability and the quantity of cars of the corresponding type is given, and the example of problem solving of supplying the freight owner with the cars of commercial availability that are not lower than needed is also proposed.Â